SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN KEPALA CABANG TERBAIK BANK SUMUT DENGAN MENERAPKAN METODE VIKOR - Hutapea, Betrik J; Mesran, Mesran; Nurhabibah, Siti (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2018)
SUMUT Bank is one of the Banks in Indonesia with the name of the company PT. Regional Development Bank of North Sumatra. The North Sumatra Bank has branches in each region in North Sumatra both in the district and in the sub-district, and each of these branches is led by a branch leader or branch head. The head of this branch is responsible for the reversal of the Bank being led. The best and most accomplished branch heads deserve more and more awards. The selection of the best branch heads is selected transparently and structured in the hope that it can be a motivation for all branch heads to be able to further improve the quality and service of the Bank they lead. Making the best branch head selection done manually will take a long time and tends to be less transparent and structured. One solution so that the implementation of the selection can be carried out easily and quickly, it requires a Decision Support System that can provide consistency of assessment. In this study the method used is the VIKOR method (Visekriterijumsko Kompromisno Rangiranje). This method makes cracking on alternatives based on criteria that have been determined with an ideal compromise solution or the best solution, so that this system can later be beneficial for the SUMUT Bank to get the title in determining the best branch head.Keywords: Decision Support System, North Sumatra Bank, Branch Head, Vikor